Clinical Implications of Early Molecular Diagnosis in Lung Cancer- brief review - Claudiu-Eduard Nistor; Camelia Stanciu-Găvan (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2020)
Lung cancer is a major issue in oncology pathology worldwide. According to the WHO, this disease is the number one cause of death in both men and women worldwide [1]. Worldwide The countries with the highest incidence of lung cancer meet in Polynesia and Hungary [2]. in Europe in 2018 According to the data provided by GLOBOCAN, the incidence of lung cancer was 470,039 new cases, of which 311,843 men and 158 196 women [3]. The highest incidence was in Hungary, Austria, Germany, Slovenia, Latvia, Romania, the last places being Portugal, Malta, Lichtenstein [4]. For the correct analysis of the survival rate of patients diagnosed with lung cancer, the tumor stage (microcellular lung cancer and non-microcellular lung cancer) were considered; histopathological type (adenocarcinoma, squamous cell carcinoma, neuroendocrine lung tumors - small cell carcinoma, carcinoid; type of treatment (surgical, surgery-chemotherapy, surgery-radiotherapy, surgery-chemo-radiotherapy) [5]. Advanced lung cancer has an extremely poor prognosis, with a 5-year survival of only 5% [6]. An early diagnosis of lung cancer is needed to increase survival. A rapid personalized diagnosis (molecular, imaging, anatomopathological, immunohistochemical) is required in order to initiate an early personalized treatment [7]. After establishing the personalized diagnosis, the therapeutic attitude in the case of lung cancer the treatment can be started [8]. In this context, Molecular diagnosis of lung cancer can be made in the early stages of the disease.